2021
DOI: 10.1111/jfpp.15762
|View full text |Cite
|
Sign up to set email alerts
|

Combining slightly acidic electrolyzed water and slurry ice to prolong the shelf‐life of mackerel ( Pneumatophorus japonicus )

Abstract: Mackerel (Pneumatophorus japonicus) is an attractive fish in Europe for the rich polyunsaturated fatty acids (PUFA), such as eicosatetraenoic acid (EPA) and docosahexaenoic acid (DHA), which demonstrate nutritional significance to the human diet (Domingo, 2016;Sumi et al., 2016). But like other aquatic products, mackerel is prone to spoilage due to biochemical reactions or storage conditions (Ezquerra-Brauer et al., 2016;Olatunde & Benjakul, 2018).Compare with flake ice, which could only cool the temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Chewiness is related to the number of chews required to swallow food (Sun et al, 2021). It was not observed that chewiness followed a clear trend in all samples during storage and Liu et al (2021) also showed the same result. However, the samples of CS2 in the late phase of storage had the highest chewiness value.…”
Section: Tpamentioning
confidence: 81%
“…Chewiness is related to the number of chews required to swallow food (Sun et al, 2021). It was not observed that chewiness followed a clear trend in all samples during storage and Liu et al (2021) also showed the same result. However, the samples of CS2 in the late phase of storage had the highest chewiness value.…”
Section: Tpamentioning
confidence: 81%
“…The myosin heavy chain (MHC, 220 kDa), actin (43 kDa), and tropomyosin (36 kDa) were the three main bands of MPs, which were closely associated to protein degradation (Cai et al ., 2020). In general, protein cross‐linking and aggregation may be responsible for the formation of heavy molecular chains, whereas the degradation of heavy molecular chains may be responsible for the formation of light molecular chains (Lin, 2021). As storage time increases, the electrophoretic band intensity in all samples decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Stable chlorine dioxide (ClO 2 ) application has gradually expanded to the food industry and agricultural product processing industry, due to its vigorous antibacterial property by selective oxidation (Ofori et al, 2018;Dong et al, 2022). Slightly acidic electrolyzed water (SAEW) is also one of the non-thermal sterilisation technologies, which electrolyzes sodium chloride solution or diluted hydrochloric acid to create hypochlorite, the main sterilising component (Lin, 2021). In addition, because of its environmental protection, low price, and strong antibacterial ability, it has attracted extensive attention (Hao et al, 2021;Lan et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…ATP and its related compounds were extracted according to the previous study [19] , which were measured by HPLC (LC-2010C HT, Shimadzu Corporation). The pH value of phosphate buffer as mobile phase was 6.5 and the flow rate was 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Significant decrease of TVB-N was found after 20 days of storage in G and USG groups compared to the CK group. According to the research of Liu et al [19] , the TVB-N value of 30 mg N/100 g could be used as an acceptable threshold for the spoilage of marine fish. At day 20, the TVB-N value of CK group came up to 21.14 mg N/100 g. The TVB-N values of the US, G, and USG groups were only 19.1, 12.2 and 10.26 mg N/100 g, respectively.…”
Section: Methodsmentioning
confidence: 99%